Concert Band and Visiting Alumni in the Annual All-Request Alumni Concert, June 1, 1961 - (:unkn) unknown (My University, 1961)
Concert program for Concert Band and Visiting Alumni in the Annual All-Request Alumni Concert, June 1, 1961